Thermodynamics and Heat Power - Granet, Irving; Alvarado, Jorge Luis; Bluestein, Maurice (CRC Press, 2021)
The ninth edition of Thermodynamics and Heat Power contains a revised sequence of thermodynamics concepts including physical properties, processes, and energy systems, to enable the attainment of learning outcomes by Engineering and Engineering Technology students taking an introductory course in thermodynamics. Built around an easily understandable approach, this updated text focuses on thermodynamics fundamentals, and explores renewable energy generation, IC engines, power plants, HVAC, and applied heat transfer. Energy, heat, and work are examined in relation to thermodynamics cycles, and the effects of fluid properties on system performance are explained. Numerous step-by-step examples and problems make this text ideal for undergraduate students. This new edition: Introduces physics-based mathematical formulations and examples in a way that enables problem-solving. Contains extensive learning features within each chapter, and basic computational exercises for in-class and laboratory activities. Includes a straightforward review of applicable calculus concepts. Uses everyday examples to foster a better understanding of thermal science and engineering concepts. This book is suitable for undergraduate students in engineering and engineering technology.